Triton Haze Analogs: The Role of Carbon Monoxide in Haze Formation. Issue 1 (17th January 2022) - Moran, Sarah E.; Hörst, Sarah M.; He, Chao; Radke, Michael J.; Sebree, Joshua A.; Izenberg, Noam R.; Vuitton, Véronique; Flandinet, Laurène; Orthous‐Daunay, François‐Régis; Wolters, Cédric
Abstract: Triton is the largest moon of the Neptune system and possesses a thin nitrogen atmosphere with trace amounts of carbon monoxide and methane, making it of similar composition to that of the dwarf planet Pluto. Like Pluto and Saturn's moon Titan, Triton has a haze layer thought to be composed of organics formed through photochemistry. Here, we perform atmospheric chamber experiments of 0.5% CO and 0.2% CH4 in N2 at 90 K and 1 mbar to generate Triton haze analogs. We then characterize the physical and chemical properties of these particles. We measure their production rate, their bulk composition with combustion analysis, their molecular composition with very high resolution mass spectrometry, and their transmission and reflectance from the optical to the near‐infrared with Fourier Transform Infrared (FTIR) Spectroscopy. We compare these properties to existing measurements of Triton's tenuous atmosphere and surface, as well as contextualize these results in view of all the small, hazy, nitrogen‐rich worlds of our solar system. We find that carbon monoxide present at greater mixing ratios than methane in the atmosphere can lead to significantly oxygen‐ and nitrogen‐rich haze materials. These Triton haze analogs have clear observable signatures in their near‐infrared spectra, which may help us differentiate the mechanisms behind haze formation processes across diverse solar system bodies. Plain Language Summary: Triton is the largest moon of the outer planet Neptune. It has a very thin atmosphere made of similar gases to the atmospheres of the dwarf planet Pluto and Saturn's moon Titan. Sunlight or high energy particles can break apart the molecules that make up these gases, which can then react to form solid particles, called hazes. We made haze particles in an atmospheric chamber under Triton‐like temperature (90 K) and atmospheric composition (small amounts of carbon monoxide and methane in molecular nitrogen), and then measured the chemical and physical properties of the resulting material. We compare our results to similar measurements of laboratory materials made for Pluto and Titan. Our results show larger oxygen and nitrogen contents for these Triton particles, suggesting that increasing carbon monoxide in the atmosphere changes the chemistry of hazes. Within the laboratory hazes, we see signatures of molecular bonds containing oxygen in the near‐infrared, which might be useful for identifying these species with future observations of or missions to Triton. Key Points: Multiple solar system bodies have complex photochemical hazes which derive from their nitrogen and carbon‐rich atmospheres We generate and measure the properties of analog hazes ("tholin") specific to Triton‐like composition and temperature Despite other similarities, Triton tholin are much more strongly oxygenated and slightly more nitrogenated than Titan and Pluto tholin